Modeling Bursty Temporal Pattern of Rumors - Kwon, Sejeong; Cha, Meeyoung (Proceedings of the International AAAI Conference on Web and Social Media, 2014)
Online social networks enable fast and wide diffusion of rumors, which could be potential threats to the society. Understanding the rumor spreading mechanism is therefore essential. This demo presents an agent-pattern based model that can explain the spiky temporal diffusion pattern of rumors. The demo platform provides an interface allowing users to check a wide set of parameters contribute to the characteristic temporal pattern of rumors.